Closed quotient as a glottal efficiency indicator - Balakrishna M.N (Journal of All India Institute of Speech and Hearing, 1970)
The study of the vibratory patterns of vocal folds has drawn attention of researchers. Recently several methods have been developed for objectivelystudying the movements of vocal folds. One of them is electroglottography. E.G.G. has many advantages over other techniques mainly because it is anon-invasive technique and permits quantification of vocal fold vibration.